Verticillium survives heat in Mojave Desert alfalfa - Donald Erwin; Amy B. Howell (California Agriculture, 1998)
Verticillium albo-atrum, the cause of Verticillium wilt of alfalfa, was detected consistently in 1989 and 1990 in alfalfa stems collected from a farm in the Mojave Desert at air temperatures (up to 104°F) above the maximum (86°F) for its growth and sporulation. According to research in other areas of the United States and in Canada, infected alfalfa hay is a prime source of inoculum. Resistance to Verticillium wilt in nondormant germplasms was readily developed by selection in six germplasms that have been released.